Government social media in Indonesia: just another information dissemination tool - Idris, Ika Karlina (Penerbit Universiti Kebangsaan Malaysia, 2018)
Indonesia is the largest social media market in Southeast Asia with approximately 79 million active users. Since 2015, government agencies have been actively using social media as one of their communication channels. This study aims to analyse whether the advent of communication technologies of social media has made Indonesia government to perform a long-term two-way communication with the citizens. The social network analysis (SNA) method was used to analyse four types of government-citizens’ conversations on social media: daily communication, campaign communication, crisis, and emergency communication. Two Indonesian government agencies’ social media accounts at the national level were selected as samples. One was a policy-based government agency and the other was a service-based agency. This study found that a two-way communication happened in a limited way, which was mainly in the daily conversation. The policy-based agency used social media as a channel to disseminate information, thus they had a low number of interactions. Although the agency allows comments from every follower on Facebook page, there was no interaction between the agency and the public. The agency apparently was more active to reply messages via Twitter. The high number of fake followers and political buzzer on Twitter support the finding that the only interest for the agency to be on Twitter was to disseminate information. Lack of interaction happened in the campaign communication, also in crisis and emergency communication — types of communication that are urgent and important.